CHARACTERIZATION OF THE AGRICULTURAL PRODUCTION IN PALMARES BASED ON CENSUSES DATA (1950-1984) - Badilla Vargas, Maynor (2014)
The next document consists essentially on a quantitative analysis of the agricultural production in the Palmares County, which is based on censuses statistics located in the period within 19501984. By the same token it also pretends to provide an alternative reading about the local history constructed from the agrarian one.